Guest-host tensions in a fractured world - Korstanje, Maximiliano E.; Kulshreshtha, Sharad Kumar (Anais Brasileiros de Estudos Turísticos, 2025)
From its outset, the tourism industry has focused its attention on host-guest’s relationships. They were historically characterized by stage of indifference, conflict and harmony. In recent years, some new paradigms have surfaced to hold that tourism should harmonize –although not always happen- the host-guest tensions. After the pandemic, host-guest tensions have been revived while taking radicalized forms. The tourist-phobia, as well as the sentiment of hostility against strangers, is part of a new fractured world where the classic spirit of hospitality is in crisis. The present paper explores the ebbs and flows of the anti-tourist discourse in a post viral context.